The Lesser Bohemians - McBride, Eimear (Random House Inc, 2016)
A young Irish drama student in 1990s London makes new friends, establishes a place for herself, and seeks to shed her plain-girl identity before entering a whirlwind affair with an older man who changes her in unexpected ways.